Inclusive Education: A Developmental Approach in Special Education - Poonam; Sangwan, Sheela (JOURNAL OF INDIAN EDUCATION, 2011)
The goal of this review paper is to examine the issues related to the provisions, practices and curricular concerns for children with Special Educational Needs (SEN) in inclusive education. The paper focuses on educational outcomes of inclusion for students with and without developmental disabilities, including studies that have measured both traditional academic outcomes (for example literacy, mathematics, etc.) and non-academic skill development in areas such as basic life skills (for example communication, motor skills, functional life skills). It also reviews the research literature related to teaching techniques and educational contexts that have been found to promote effective inclusion (i.e., to provide optimal learning for all students, both with and without developmental disabilities).